Même et autre : de White Rock Line (1990) à White Rock Line (1990, remade 2014) - Anne Cadenet (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Exposed to the climates for more than twenty years, White Rock Line gradually became « naturally » grey. This meant that it no longer conformed to the definition given to the sculpture in 1990; a line of white stones forming a sculpture 40 metres long and 1 metre 50 centimetres wide. After studying several restoration options, the substitution of the 18 tonnes of limestone is envisaged and approved of by the artist in the folowing terms : « I share your idea of remaking the piece with new stones from the original quarry. »